Vehicle Speed Control Using Gain Scheduling PID with Experimental Throttle-in-the-Loop - Abdul Kadir, Faizul Akmar; Tamaldin, Noreffendy; Ayob, Md Razali; ABDULLAH, Mohd Azman; HUDHA, Khisbullah; Mat Yamin, Ahmad Kamal (Praise Worthy Prize, 2014)
This paper presents a control strategy for controlling speed of a vehicle experiencing the disturbance from road gradient. A non-linear vehicle longitudinal model is developed as plant for modelling the vehicle behaviour in longitudinal direction with Electronic Throttle Body (ETB) is introduced as the inner-loop subsystem. The vehicle is subjected to several positive (uphill) road gradient disturbances with gain scheduling Proportional-Integral-Derivative (PID) controller is proposed to control the vehicle speed. The simulation result is then validated using experimental throttle-in-the-loop method. MATLAB-SIMULINK is chosen as a simulation tool to simulate the vehicle dynamics behaviour and evaluate the performance of the control structure. The result shows that the proposed controller is able to effectively control the vehicle speed by reducing the speed drop during uphill travel and its performance is much better than fixed gain PID controller. The simulation results agree well with experimental.